Development of a Microfluidic Device to Improve Microfiltration Process - Rohyani, Achmad; Schmitz, Philippe; Lafforgue, Christine (IPTEK Journal of Proceedings Series, 2014)
When neutrally buoyant particles are subjected in laminar and continuous flow, one can observe that particles generally migrate across the streamlines in a particular way. Such lateral motion called â€œtubular-pinched effectâ€ causes particles tend to migrate toward micro channel wall. The origin of this motion is due to the parabolic nature of the laminar velocity profile in Poiseuille flow. This phenomenon produces a shear-induced inertial lift forces which allows the scattered particles focused and form narrow annulus near the wall. The focalization of particles could improve the method of separation process by using microfiltration. Then, micro porous membrane is used for microfiltration which filters focused particles from a fluid by passage through it. In this work, we use this lift forces generated in laminar microfluidic systems to focus randomly distributed particles continuously. The form of particles deposition poon micro porous membrane hence was observed to determine the important parameter influencing the equilibrium position of the particles. A numerical simulation (COMSOL Multiphysics Â®) has also first been developed to study the influence of channel and on the subsequent size of annulus formed by the focused particles on the membrane.